The Influence of Online Customer Reviews and Online Customer Ratings on Purchase Decisions on Tokopedia: A Case Study of Benua Melayu Darat District - Widjaya, Ferdy; Aodi, Markus (Technology, Business and Entrepreneurship, 2024)
This study aims to analyze the influence of online customer reviews and online customer ratings on product purchase decisions on the e-commerce platform Tokopedia. This research is a quantitative study using non-probability sampling techniques with a purposive sampling approach. The sample size in this study was determined using Cochran's formula, resulting in 96 respondents who are residents of Benua Melayu Darat District, users of Tokopedia. Data was collected by distributing questionnaires to respondents via Google Forms. The data analysis techniques used in this study include instrument testing, classical assumption tests, multiple linear regression analysis, and hypothesis testing, all conducted using SPSS 26. The results of this study indicate that, simultaneously, online customer reviews and online customer ratings significantly influence purchase decisions. Partial results show that both online customer reviews and online customer ratings have a significant effect on purchase decisions. Overall, the findings demonstrate that online customer reviews and online customer ratings positively and significantly affect product purchase decisions on the Tokopedia e-commerce platform.